Character of Student Learning Independence in Mathematics Subjects in Elementary Schools - Azwa, Lailatul; Alik Mustafidal Laili, (Jurnal Pendidikan Tambusai, 2023)
The purpose of this research is to describe the character of learning independence of fourth grade students in mathematics subjects at SD Negeri 1 Sanggrahan. Learning independence needs to be developed and considered. Although learning independence is important to develop, generally students still have quite low learning independence. Learning independence is an important factor when determining student success when learning, especially in mathematics subjects that require practice and experience to solve problems in mathematics. In math lessons, learning independence is needed to increase the enthusiasm for learning in students. The type of research used is qualitative research. Data collection techniques using questionnaires, interviews, and documentation. Data analysis techniques using data reduction techniques, data presentation, and conclusion drawing. Based on the results of research and discussion, it can be concluded that the character of learning independence of fourth grade students in mathematics subjects is included in the good category, namely 75% referring to 9 indicators. Of the 9 indicators, there are 2 categories in class IV students, namely very good (81%-100%) in indicator 2 and 8 other indicators included in the good category (61%-80%). In addition, students in the very good category (81%-100%) totaled 4 students, the good category (61%-80%) totaled 21 students, the good enough category (41%-60%) totaled 2 students.